The effect of a single dose of morphine on muscle fatigue indices in male rats - Sedigheh Amiresmaili; Massoud Mobini; Ali Roohbakhsh; Ali Shamsizadeh; Fatemeh Amin; Mohammad Allahtavakoli (مجله دانشگاه علوم پزشکی بیرجند, 2016)
Background and Aim: Endogenous opioids and addictive opiate drugs change many body functions. . Previous studies have referred to the effects of morphine on smooth and pulmonary muscles ., but the  effects of opioids on skeletal muscles is not known well. Thus, the current study aimed at assessing the effect of a single dose of morphine on muscle fatigue in male rats.